2005
DOI: 10.1111/j.1939-165x.2005.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of latex agglutination kits for detection of fibrin(ogen) degradation products and D‐dimer in healthy horses and horses with severe colic

Abstract: Commercial latex-agglutination D-dimer assays might prove useful as adjunctive tests for the diagnosis of DIC in horses with severe colic; however FDP assays are invalid for this purpose. Low AT activity and prolonged aPTT at admission are associated with a poor prognosis in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 24 publications
2
38
0
1
Order By: Relevance
“…A hypercoagulation state is usually developed during the progress of colic in horses and it refers to disseminating intravascular coagulation (DIC) (Cesarini et al, 2010). The hypercoagulation and increased fibrinolysis can be assessed by measuring the concentration of plasma D-dimer, which is very useful in acute gastrointestinal disorders, laminitis and in septic foals (Stokol et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A hypercoagulation state is usually developed during the progress of colic in horses and it refers to disseminating intravascular coagulation (DIC) (Cesarini et al, 2010). The hypercoagulation and increased fibrinolysis can be assessed by measuring the concentration of plasma D-dimer, which is very useful in acute gastrointestinal disorders, laminitis and in septic foals (Stokol et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Tinker et al (1997) stated that there were no association between gender and incidence of colic.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…In this context, the best indicator of a negative prognosis for the admission of horses with colic are a prolonged time of aPTT (>63 seconds) together with low antithrombin activity (< 74%) (Stokol et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among these methods, JOURNAL OF THE HELLENIC VETERINARY MEDICAL SOCIETY 2010,61(1) ΠΕΡΙΟΔΙΚΟ ΤΗΣ ΕΛΛΗΝΙΚΗΣ ΚΤΗΝΙΑΤΡΙΚΗΣ ΕΤΑΙΡΕΙΑΣ 2010,61(1) those based on the enzyme-linked immunosorbent assay (ELISA) and agglutination (latex agglutination or immune-turbidimetric assay) are the most commonly used (Caldin et al 2000, Stokol et al 2005, Boutet et al 2009). …”
Section: Methods For D-dimer Determinationmentioning
confidence: 99%
“…Furthermore, it was found that healthy horses have detectable concentrations of serum FDPs and D-dimer and a high D-dimer concentration supports the diagnosis of DIC, while FDPs were not useful for the diagnosis of DIC in this species (Sandholm et al 1995, Stokol et al 2005). …”
Section: ξητί-ξχι-β-1 Chcfmsrmentioning
confidence: 99%